Efforts To Improve Indonesian Language Learning Outcomes in Reading Short Stories Using The Reading Guide Strategy for Students SDN 105308 Namo Bintang Deli Serdang - Sembiring Depari, Susan Andriani; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This study aims to improve Indonesian language learning outcomes in short story reading through the implementation of the Reading Guide strategy among fourth-grade students at SDN 105308 Namo Bintang, Deli Serdang Regency, in the 2025-2026 academic year. The research questions addressed are how the Reading Guide strategy is implemented in short story reading instruction and whether this strategy can enhance students' learning outcomes. This study employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, consisting of two cycles. Each cycle included planning, action implementation, observation, and reflection. The research subjects comprised 20 fourth-grade students, including 7 boys and 13 girls. Data collection techniques included observation, documentation, and learning outcome tests. Data were analyzed using descriptive quantitative techniques to assess improvements in students' learning outcomes. The findings indicate a significant improvement in students' learning outcomes following the implementation of the Reading Guide strategy. In the pre-cycle phase, only 20% of students achieved a score of ≥70. After the first cycle, this increased to 50%, and by the second cycle, 80% of students achieved good and excellent categories. Student engagement in learning also increased from 50% in the first cycle to 85% in the second cycle. These results demonstrate that the Reading Guide strategy not only enhances students' comprehension of short story texts but also encourages active participation in learning. Thus, this study confirms that the Reading Guide strategy is effective in improving students' learning outcomes in short story reading. This strategy can be an alternative in Indonesian language instruction to help students understand reading materials in a more structured and in-depth manner